Polyphenolic Extract from Sambucus ebulus L. Leaves Free and Loaded into Lipid Vesicles - Ramona-Daniela Păvăloiu; Fawzia Sha’at; Corina Bubueanu; Mihaela Deaconu; Georgeta Neagu; Mousa Sha’at; Mihai Anastasescu; Mona Mihailescu; Cristian Matei; Gheorghe Nechifor; Daniela Berger (Nanomaterials, 2019)
The paper deals with the preparation and characterisation of hydroalcoholic polyphenolic extract from Sambucus ebulus (SE) leaves that was further loaded into three-types of lipid vesicles: liposomes, transfersomes, and ethosomes, to improve its bioavailability and achieve an optimum pharmacological effect. For Sambucus ebulus L.-loaded lipid vesicles, the entrapment efficiency, particle size, polydispersity index and stability were determined. All prepared lipid vesicles showed a good entrapment efficiency, in the range of 75−85%, nanometric size, low polydispersity indexes, and good stability over three months at 4 °C. The in vitro polyphenols released from lipid vehicles demonstrated slower kinetics when compared to the free extract dissolution in phosphate buffer solution at pH 7.4. Either free SE extract or SE extract loaded into lipid vesicles demonstrated a cytoprotective effect, even at low concentration, 5 ug/mL, against hydrogen peroxide-induced toxicity on L-929 mouse fibroblasts’ cell lines. However, the cytoprotective effect depended on the time of the cells pre-treatment with SE extract before exposure to a hydrogen peroxide solution of 50 mM concentration, requiring at least 12 h of pre-treatment with polyphenols with radical scavenging capacity.